A Characterization of Periodicity in the Voltage Time Series of a Riometer. Issue 7 (4th July 2020) - Marshall, F. A.; Thomson, D. J.; Chave, A. D.; Fiori, R. A. D.; Danskin, D. W.
Abstract: This paper reveals unprecedented periodicity in the voltage series of relative ionospheric opacity meters (riometers) of the Canadian Riometer Array (CRA). In quiet times, the riometer voltage series is accurately modeled by a stochastic process whose components include both a six term expansion in harmonic functions and some amplitude modulated modes of lower signal to noise ratio (SNR). In units of cycles per sidereal day (cpsd), the frequencies of the six harmonic functions lie within 0.01 cpsd of an integer. Earth's rotation induces a splitting of the low SNR components, resulting in the appearance of nine multiplets in standardized power spectrum estimates of the considered CRA voltage series. A second feature of these spectrum estimates is a 6 min periodic element appearing in both the CRA voltage series and the proton mass density series of the Advanced Composition Explorer (ACE). Spectral peak frequencies have been detected, which lie near established solar mode frequency estimates. In addition, some of these peak frequency estimates are coincident with peak frequency estimates of the standardized power spectra for the time series of proton mass density and interplanetary magnetic field strength (IMF) at ACE. Key Points: The voltage series of a riometer is accurately modeled by a stochastic process including a harmonic function expansion component The power spectrum estimate for the voltage series contains multiplets centered near the harmonic frequencies of one cycle per sidereal day Several of the detected spectral peak frequencies lie near established solar mode frequency estimates